English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4x + -3y = -12

^solve for y


thank you!

2007-01-01 13:38:34 · 9 answers · asked by Anonymous in Science & Mathematics Mathematics

9 answers

To solve for y, you need to get it by itself in the equation.

Start with the easiest: subtract something from both sides - 4x
then
-3y = -12 - 4x

Then to get y by itself, divide both sides by -3
-3y/(-3) = -12/-3 - 4x/-3
or
y = 4 + 4/3x
That is as close as you can come to a solution

2007-01-01 13:45:18 · answer #1 · answered by firefly 6 · 1 1

This is not hard, get y on one side of the = sign and the rest on the other

- 3y = - 12 - 4x (you subtract 4x from each side)

-y = -12/3 - 4x/3 (divide each side by 3)

y = 12/3 + 4x/3 (multiply each side by -1)

y = 4 + 4x/3
Done

2007-01-01 21:52:35 · answer #2 · answered by Anonymous · 0 0

You need to isolate the y. The first thing on the left side that is not 'y' is 4x. Subtract it and take it to the other side.

-3y = -12 - 4x

Now there is a -3 multiplied by y. To get rid of it, divide by -3.

y = (-12 - 4x) / -3

Now on the right side, this can be simplified.

y = -12/-3 + -4x/-3
y = 4 + 4/3x

Hope that helps!

2007-01-01 21:46:58 · answer #3 · answered by teekshi33 4 · 0 0

4x + -3y = -12
4x-3y=-12 add 3y+12 to each side
4x+12=3y divide both sides by 3
y=4x/3+4

2007-01-01 22:40:12 · answer #4 · answered by yupchagee 7 · 0 0

-3y=-4x-12~subtracted 4x from both sides to get 3y by itself
y=4x/3+4~divided everything by -3 to just get y

2007-01-01 22:20:03 · answer #5 · answered by jerseygirl 2 · 0 0

4x + -3y = -12

-4x -4x (subtract 4x from each side)

-3y= -12 - 4x

/-3 /-3 (divide both sides and everything by -3)

therefore: y= 4 - ( 4/-3 X x)

2007-01-01 21:54:19 · answer #6 · answered by Kiara 5 · 0 0

get the y term on a side by itself and divide by it's coefficient to get the y.


4x + -3y = -12
4x + -3y -4x = -12 - 4x
-3y = -12- 4x
-3y/-3 = (-12 -4x)/-3
y = 4+ 4/3x

2007-01-01 22:28:19 · answer #7 · answered by chevygirl0130 1 · 0 0

4x + -3y = -12
4x + -3y + -4x = -12 + -4x
-3y / -3 = (-12 / -3) + (-4x / -3)

i think you can do it from there hope that was helpful

2007-01-01 21:50:09 · answer #8 · answered by Love; ♥ 2 · 0 0

y=4x/3 + 4

you need another equation to eliminate x.

2007-01-01 21:49:01 · answer #9 · answered by Barry N 2 · 0 0

fedest.com, questions and answers